2019
DOI: 10.7554/elife.46902
|View full text |Cite
|
Sign up to set email alerts
|

Contractile acto-myosin network on nuclear envelope remnants positions human chromosomes for mitosis

Abstract: To ensure proper segregation during mitosis, chromosomes must be efficiently captured by spindle microtubules and subsequently aligned on the mitotic spindle. The efficacy of chromosome interaction with the spindle can be influenced by how widely chromosomes are scattered in space. Here, we quantify chromosome-scattering volume (CSV) and find that it is reduced soon after nuclear envelope breakdown (NEBD) in human cells. The CSV reduction occurs primarily independently of microtubules and is therefore not an o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 30 publications
(32 reference statements)
3
46
0
Order By: Relevance
“…It is important to note that there are changes in cell physiology just with time growing in culture. For example, Seaman et al have found that the nuclear morphology changes significantly over time in cultured human primary fibroblast cells [ 44 ]. Indeed, in our data both the GFP-KDEL and SUN1L-KDEL cells at 1G ( Table 1 ) show expected decrease in nuclear area and increase in nuclear height when comparing data from 2 h and 20 h in culture.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that there are changes in cell physiology just with time growing in culture. For example, Seaman et al have found that the nuclear morphology changes significantly over time in cultured human primary fibroblast cells [ 44 ]. Indeed, in our data both the GFP-KDEL and SUN1L-KDEL cells at 1G ( Table 1 ) show expected decrease in nuclear area and increase in nuclear height when comparing data from 2 h and 20 h in culture.…”
Section: Discussionmentioning
confidence: 99%
“…We identified myosin IIA activity and the actin cytoskeleton as important for epidermal differentiation and Lamin A/C dispersal. Myosin II activity is required for nuclear repositioning in cell migration (Gomes, Jani, and Gundersen 2005), constriction of the cytokinetic actomyosin contractile ring (Powell 2005;De Lozanne and Spudich 1987;Mabuchi 1977) and contraction of an actin network around the nucleus at nuclear envelope breakdown (Booth et al 2019). Arp2/3, required for branched actin filament nucleation, has previously been identified as required for epidermal differentiation (Lechler 2014;Zhou et al 2013), regulation of nuclear actin (Oma and Harata 2011) and correct formation of the actomyosin contractile ring in cell division (Chan et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…, 2014 ; Plessner et al. , 2019 ), and its accumulation on the nuclear envelope (NE) facilitates chromosome congression ( Booth et al. , 2019 ).…”
Section: Introductionmentioning
confidence: 99%